MAKNA KOSAKATA BAHASA INGGRIS DI DALAM TEKS BERBAHASA ARAB - Astari, Rika (Jurnal CMES, 2015)
This research is purposed to elaborate the structure of meaning alteration which takes place in the English vocabulary in the Arabic language texts. This research is using the qualitative descriptive method and an componential meaning approach. This analysis was concluded that the English vocabulary in the Arabic language text has first meaning and second meaning or lexical meaning using the diverge of context, based on the context of sentences and the society as the user of the language. The meaning changing in the English vocabulary which are found in Arabic texts can be the addition of meaning element, the equation of meaning element, the changing of polysemy becomes monosemy, and the shifting of English vocabulary meaning in the Arabic language. The addition of meaning element in the English vocabularies in the Arabic language is caused by the using of idiom in a certain word and also the factor of requirement for the sentences context in the language of media. In the other hand, the equation of meaning element is caused by that the Arabic language has not the term and in behalf of the easy communication and the reader’s comprehension in the language of media. The changing of polysemy into monosemy is caused by that the Arabic language has not the lexicon to show the certain meaning without using the English vocabularies. Finally, the shifting of meaning in the English vocabulary in the Arabic language is caused by the word as the name of private use for food.